Effectiveness of ultrasonic activation associated to glycolic acid on smear layer removal, dentin structure and bond strength to root dentin (Bioscience Journal, 2023)
This study evaluated the effects of ultrasonic activation (US) associated to glycolic acid (GA) on smear layer, dentin structure and bond strength (BS) of filling/restorative material to root dentin. The roots were used for antimicrobial activity, dentin structure and BS evaluation, being distributed into seven groups, according to irrigation protocols: G1:DW+US; G2:17% EDTA; G3:QMix; G4:17% GA; G5:17% EDTA+US; G6:QMix+US; G7:17% GA+US. Scanning electronic microscopy, transmission electronic microscopy and push-out were performed, with specific statistical analysis for each evaluation. The highest smear layer removal occured in Groups 6 and 7 (p0.05). The highest BS of filling and restorative material occurred in Groups 6 and 7, and Groups 5, 6 and 7, respectively, being similars between them (p>0.05). The use of GA+US promoted effective smear layer removal and dentin structure preservation, improving the BS of filling/restorative material to root dentin.